Risk and sanitary safety: analysis on medical product reprocessing in hospitals in Salvador, Northeastern Brazil - Costa, Eliana Auxiliadora Magalhães; Costa, Ediná Alves (Revista de Saúde Pública, 2012)
OBJECTIVE: To analyze the technical conditions for medical product reprocessing in hospitals. METHODS: This was a descriptive study on multiple cases in materials and sterilization centers at four hospitals in the city of Salvador, Southeastern Brazil, in 2010. Semi-structured interviews were conducted and direct observations were made, based on a regulatory model for medical product reprocessing that was drawn up with the technique of consensus verification as the reference standard. The analytical categories used in this study were: management of the practice of medical product reprocessing; reprocessing protocols; monitoring of the sterilization process; and capacity for product tracking. These categories were scored according to their degree of conformity with the regulatory model for reprocessing used. RESULTS: General inadequacy of the technical conditions for medical product reprocessing was observed, with regard to the structural conditions of the materials and sterilization centers studied and the work process conditions, along with organizational and managerial difficulties that interfered with the practices analyzed. CONCLUSIONS: The practices of medical product reprocessing in the hospitals analyzed constitute a risk for the patient users. Risk management systems need to be introduced in these hospitals, with greater sanitary control by the state, in order to protect patients' health.